The Experience of Using a Combination of Febuxostat and Canakinumab in Tophaceous Gout Complicated by Chronic Kidney Disease in a Teenage Patient: A Case Study - Maria I. Kaleda; Irina P. Nikishina; Nurali Z. Zokirov; Alina V. Charlamova; Maxim S. Eliseev (Вопросы современной педиатрии)
Background. Gout is extremely rare in childhood and is genetically determined in almost all cases. Late initiation of urate-lowering therapy in children with gout increases the risk of severe disability due to the state of the musculoskeletal system and kidney function. Description of a Clinical Case. At the age of 13 years and 9 months, the boy first experienced acute pain, hyperthermia, and restriction of movement in the right elbow joint. Acute haematogenous osteomyelitis was excluded. Further, repeated recurrences of arthritis of the 1st metatarsophalangeal joint of the left foot, distal interphalangeal joints of the 3rd and 5th fingers of the right hand were noted. After 8 months,  a diagnosis  of 'Rheumatoid  arthritis,  polyarticular  type' was established  at his place of residence.  Hyperuricemia (0.99 μmol/L), high serum levels of creatinine (127 μmol/L) and urea (7.2 μmol/L), hypoisostenuria (1,008–1,009)  were detected for the first time. Nephrological examinations were not conducted. He received non-steroidal  anti-inflammatory  drugs and sulfasalazine without effect, with increasing deformity in the affected joints. At the age of 15 years and 7 months, gout was diagnosed with damage to the joints and kidneys, allopurinol therapy was initiated. Normalization of serum uric acid levels was not reached, repeated attacks of gouty arthritis were noted. Direct automated sequencing of the coding sequence of the HPRT1 gene, including exon-intron  regions, revealed a mutation of c.481G>А (p.Aia161Thr)CM088136 NM 000194.1 in the hemizygous state. Genetically determined tophaceous gout,  stage  2–3  chronic  kidney  disease  were  diagnosed.  The  patient  was  administered  the  interleukin-1  inhibitor  canakinumab (single injection), urate-lowering  therapy with a non-purine  inhibitor of xanthine oxidase febuxostat  was prescribed.  As a result, the target serum uric acid level was reached a week later. Over the next 7 months, there were no repeated gouty attacks. Conclusion. Late initiation of treatment for tophaceous gout in the teenage patient caused chronic kidney disease. The successful experience of using a combination of canakinumab and febuxostat in a patient under 18 years old has been described for the first time.